Democracy, Public Expenditures, and the Poor - Keefer, Philip; Khemani, Stuti (World Bank, Washington, DC, 2014)
Countries vary systematically with respect to the incentives of politicians to provide broad public goods, and to reduce poverty. Even in developing countries that are democracies, politicians often have incentives to divert resources to political rents, and to private transfers that benefit a few citizens at the expense of many. These distortions can be traced to imperfections in political markets, that are greater in some countries than in others. The authors review the theory, and evidence on the impact of incomplete information of voters, the lack of credibility of political promises, and social polarization on political incentives. They argue that the effects of these imperfections are large, but that their implications are insufficiently integrated into the design of policy reforms aimed at improving the provision of public goods, and reducing poverty.